Sources of innovation: Consequences for knowledge production and transfer - Sarah Philipson (Journal of Innovation & Knowledge (JIK), 2020)
In his groundbreaking work Sources of Innovation, Eric von Hippel discussed from where in (and out of) the value-chain innovations came in different industries: the customer, the manufacturer, the supplier, or third-party innovator (universities, research laboratories, etc.). The world has changed, and new phenomena have become apparent. This article is a conceptual paper that discusses these new phenomena and presents a tentative updated pheno-typology of the sources of innovation, adding six to von Hippel's original four. To build these phenotypes it draws heavily on Kaulio (1998), Borrus and Zysman (1997) and Hart & Kim (2002). As principal take-away, the consequences for knowledge production and transfer are discussed for each of the 10 phenotypes, in comparison to the in-house, non-open innovation, default phenotype.
Keywords: O31; O32; 650; Differentiation; Innovation; Monopoly rent; Sources of innovation; Tacit knowing